(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Landicho LD, Ocampo MTNP, Cabahug RED, Abadillos MG, Cosico RSA, Castillo AKA, Ramirez MAJP, Laruan KA. 2021. Local knowledge and practices towards the ecological restoration of selected landscape in Atok, Benguet, Philippines. Biodiversitas 22: 2785-2794. This study argues that local ecological knowledge and practices contribute to forest conservation and management efforts. This argument is based on the research conducted in upland communities in Atok, Benguet, Philippines. Interviews, farm visits, and focus group discussions revealed that the local communities have been dependent on the forest resources within the watershed in their agricultural production activities. These local communities employed their knowledge and practices towards restoring the ecological state of the watershed. These include the integration of trees on the farm, planting of Alnus japonica for soil and water conservation, the establishment of structural soil and water conservation, maintenance of communal forests, and awareness building among the youth on forest conservation and management. A moderate level of biodiversity and evenness index were in the conservation of giant tree ferns. A very low (0.9718) diversity index and a very high (0.825) evenness index were recorded in the farm lots, while a very low (0.437) diversity index and moderate (0.421) evenness index were measured in the communal forests. On the other hand, high soil organic matter contents of 6.49% and 5.86% were recorded both at the community and farm lots, respectively. Results imply the need to sustain the use of local knowledge and practices in combination with the technological interventions from academia and research institutions to enhance the ecological restoration of forest landscapes.